Collection Development in University Libraries: Policy and Procedures - Parameswaran, M. (DESIDOC Journal of Library & Information Technology, 2003)
This article defines Collection Development in university libraries and discusses centralised and decentralised patterns. It also suggests a policy for collection development and concludes that involvement of all the staff members of the library is essential to develop a balanced collection. ary is essential to develop a balanced collection. http://dx.doi.org/10.14429/dbit.17.2.3328